Preparation method of gradient structure carbon fiber reinforced ceramic modified composite material

CN123003308APending Publication Date: 2026-10-30CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611495268.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但大量的网胎层和针刺工艺也导致预制体内部连续纤维含量降低,最终导致其力学性能相对有限

Benefits of technology

[0063](1)精确控制梯度结构:通过“单向CVI”和“单向RMI”两个关键步骤的协同作用,本发明能够精确控制复合材料内部密度和陶瓷相的梯度分布。单向CVI工艺通过控制反应气体流向和CVI增密温度等,可在C/C复合材料增密阶段形成了精确密度梯度;随后的单向RMI工艺则利用该密度梯度,引导熔融金属仅从低密度区渗入,最终形成陶瓷相从熔渗近端至熔渗远端逐渐减少的梯度结构。此制备工艺设计思路清晰、可控性强。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003308A_ABST
    Figure CN123003308A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a gradient structure carbon fiber reinforced ceramic modified composite material. Five surfaces of a carbon fiber blank are wrapped without gaps, and only one surface is left uncovered to form an exposed surface; then the carbon fiber blank is clamped in a clamping cavity of a deposition tool, placed in a chemical vapor deposition furnace, and subjected to unidirectional chemical vapor deposition, so that a C / C porous body with a density gradient decreasing from the exposed surface to the opposite surface is obtained. Then the gradient structure C / C porous body is placed in a graphite crucible with the low-density surface facing upward and the high-density surface facing downward, a graphite frame is placed above the low-density surface, and a sintering raw material is laid in the frame, so that unidirectional reaction sintering is performed, and a gradient structure carbon fiber reinforced ceramic composite material with the upper layer modified by a ceramic phase and the lower layer maintaining a C / C structure is obtained. The application has the advantages of simple technological process, convenient operation, low equipment requirement, and the obtained composite material capable of simultaneously meeting the ablation protection and high-temperature mechanical bearing requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon fiber reinforced composite material preparation technology, specifically relating to a method for preparing gradient structure carbon fiber reinforced ceramic modified composite material. Background Technology

[0002] Carbon fiber reinforced composites, prepared using carbon fibers and their fabrics as reinforcements, possess low density, high specific strength and specific modulus, as well as excellent high-temperature mechanical properties, and are widely used in the aerospace field, such as rocket engines, aircraft brake discs, nose cones and wings of hypersonic vehicles. However, carbon fiber preforms are sensitive to high temperatures and will rapidly oxidize and be lost in high-temperature oxidizing environments, ultimately leading to material failure. Since the aforementioned carbon fiber reinforced composites are mostly used in high-temperature and oxygen-containing environments, improving the oxidation resistance and ablation protection properties of carbon fiber reinforced composites is fundamental to the stable use of these materials.

[0003] Matrix modification technology is a method to effectively improve the thermal protection performance of carbon fiber reinforced composites. This method introduces a ceramic phase into the pores of the C / C preform, giving the entire material excellent ablation protection properties. However, the protective performance of the composite material prepared by this method is closely related to the content of the ceramic phase. Low-density C / C preforms have higher porosity, allowing for the introduction of more ceramic phases during matrix modification, ultimately resulting in superior burn protection performance. However, a higher ceramic phase content also increases the overall density and weight of the composite material. Currently, in most carbon fiber reinforced ceramic modified composites, the ceramic phase is mostly uniformly distributed throughout the composite material. However, in actual service, only the carbon fiber reinforced composite material on the ablation protection side plays its ablation protection role, while the ceramic phase on the inner side provides extremely limited ablation protection for the entire material. Therefore, during actual melting and infiltration, the inner ceramic phase leads to an increase in the overall density and weight of the material, but fails to provide sufficient ablation protection.

[0004] Furthermore, current carbon fiber reinforced preform structures used for matrix modification are mostly needle-punched structures, whose internal chopped fiber layers can accommodate a large amount of ceramic phase to achieve ablation protection. However, the large number of mesh layers and the needle-punching process also reduce the continuous fiber content inside the preform, ultimately resulting in relatively limited mechanical properties. During the service life of the material, not only are excellent ablation protection properties required, but also the best possible mechanical load-bearing capacity.

[0005] To overcome the aforementioned problems in the prior art, the present invention aims to provide a method for preparing gradient-structure carbon fiber reinforced ceramic matrix modified composite materials that can simultaneously meet the requirements of surface ablation protection and overall material weight reduction. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing gradient-structure carbon fiber reinforced ceramic modified composite materials. This invention utilizes unidirectional CVI synergistic unidirectional reactive infiltration (RMI) to controllably obtain gradient-structure carbon fiber reinforced ceramic modified composite materials with multiple gradient characteristics.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] The present invention discloses a method for preparing a gradient structure carbon fiber reinforced ceramic modified composite material. The method involves seamlessly wrapping five sides of a carbon fiber preform, leaving only one side uncovered to form an exposed surface. The preform is then clamped in the clamping cavity of a deposition fixture and placed in a chemical vapor deposition furnace for unidirectional chemical vapor deposition. This yields a carbon-carbon porous body with a decreasing density gradient from the exposed surface to the exposed surface. The gradient structure carbon-carbon porous body is then placed in a graphite crucible with the low-density surface facing upwards and the high-density surface facing downwards. A graphite frame is placed above the low-density surface, and a melting infiltration material is laid inside the frame for unidirectional reactive melting infiltration, thus obtaining the gradient structure carbon fiber reinforced ceramic modified composite material.

[0009] The deposition fixture includes a solid graphite plate and a porous graphite plate stacked on top of each other, with a clamping cavity formed between the solid graphite plate and the porous graphite plate for clamping the carbon fiber preform; during clamping, the exposed surface of the carbon fiber preform is controlled to be located on one side of the porous graphite plate.

[0010] The preparation method of this invention involves seamlessly wrapping the side and four sides requiring low density with graphite paper, exposing only the side where CVI deposition is needed to form a high-density C / C composite material. The side requiring high density is then fitted with a porous graphite fixture for clamping. After the preform is clamped in the clamping cavity of the deposition fixture, it is placed in a chemical vapor deposition furnace for unidirectional chemical vapor deposition. During deposition, the reactive gas can only diffuse through the pores of the porous graphite fixture, infiltrating into the carbon fiber preform from the side requiring high density. This results in a carbon-carbon porous body with a density gradient, where the side fitted with the porous graphite fixture has high density, while the side wrapped with graphite paper maintains a lower density. After completing all CVI densification processes, the gradient-structured carbon-carbon porous body is placed in a graphite crucible with the low-density side facing up and the high-density side facing down. A bottomless graphite frame is then placed above the low-density side, and a melt-infiltrating metal material is laid inside the graphite frame for unidirectional reactive melt-infiltrating. During the melting and infiltration process, the molten metal spontaneously infiltrates unidirectionally from the low-density side into the C / C porous body, forming a single-stage process, ultimately obtaining a gradient structure carbon fiber reinforced ceramic modified composite material with dual gradient characteristics of density gradient and ceramic phase gradient.

[0011] Experiments have shown that during CVI deposition, all surfaces except the exposed surface must be wrapped with graphite paper. In practice, graphite fixtures, carbon felt, and graphite strips can be added for fixation, ensuring a tight, seamless fit between the graphite paper and the preform. This seals the pores on these surfaces, preventing reactant gases from seeping into the preform through these pores during CVI. Consequently, during chemical deposition, the carbon source gas can only penetrate unidirectionally from the porous graphite plate in the deposition fixture through the exposed surface. This achieves unidirectional chemical deposition, resulting in a porous carbon-carbon body with a unidirectional gradient of density from the exposed surface to the relatively unexposed surface. Failure to use graphite paper, or the presence of gaps in the wrapping, will disrupt this unidirectional gradient.

[0012] In this invention, the carbon fiber preform can be either a conventional ungradient carbon fiber preform or a gradient carbon fiber preform.

[0013] In a preferred embodiment, the carbon fiber preform is selected from one of the following: a non-gradient carbon fiber preform, a gradient-structured 2.5-needle-punched carbon fiber preform, and a gradient-structured needle-punched-stitched carbon fiber preform.

[0014] In a further preferred embodiment, the 2.5D needle-punched carbon fiber preform with the gradient structure is obtained by alternating layers of non-woven fabric and mesh layer, and continuous needle-punching in the Z direction. In the 2.5D needle-punched carbon fiber preform, the thickness of the mesh layer increases from 0.2~0.6mm at the bottom to 0.8~2mm at the top.

[0015] In a further preferred embodiment, the carbon fiber preform is selected from a gradient-structured needle-punched-stitched carbon fiber preform; the needle-punched-stitched carbon fiber preform is a composite of a stitched carbon fiber preform and a 2.5D needle-punched carbon fiber preform; the exposed surface is the end face of the stitched carbon fiber preform.

[0016] A further preferred embodiment of the method for preparing the gradient-structured needle-punched-stitched carbon fiber preform includes the following steps:

[0017] S1 involves layering several carbon fiber woven fabrics and then stitching them together in the Z direction using continuous fibers to obtain a laminated and stitched carbon fiber preform.

[0018] S2 combines the laminated and stitched carbon fiber preform with the 2.5D needle-punched carbon fiber preform. The composite method is as follows: first, a 2.5D needle-punched carbon fiber preform is prepared, then the 2.5D needle-punched carbon fiber preform is laminated with the laminated and stitched carbon fiber preform, and then continuous fibers are used for Z-direction stitching.

[0019] Alternatively, on one side of the laminated carbon fiber preform, layers of non-woven fabric and mesh are alternately laid and needle-punched together; then continuous carbon fiber is used for Z-direction stitching.

[0020] Experiments revealed that the needle-punched carbon fiber preform consists of a continuous non-woven layer of carbon fibers, a mesh layer composed of chopped fibers, and Z-axis fibers inserted into the preform during the needle-punching process. The pores in the needle-punched preform mainly exist in the mesh layer and the Z-axis interconnected pores formed when the needles puncture the non-woven fabric. Furthermore, needle penetration can damage or even break the carbon fibers in the non-woven layer, limiting the length of the continuous fibers within the non-woven layer to the needle-punching density. Due to the high porosity of the mesh layer in the needle-punched preform, and the large number of Z-axis interconnected pores formed by needle punching, ceramics can fully fill the pores of the preform during modification. This full filling of ceramics effectively encapsulates the carbon fibers, providing adequate protection, which typically results in excellent ablation protection properties in such composite materials. However, the full filling of the ceramic phase also presents structural risks. The full filling of the pores throughout the preform means that even the inner regions in the non-ablation high-temperature environment are filled with a large amount of ceramic phase. The inner ceramic phase does not participate in ablation protection but significantly increases the density and weight of the component, resulting in a mismatch between function and density. Meanwhile, the damage to the continuous fibers in the non-woven fabric layer caused by the needle-punching process further limits the material's mechanical load-bearing capacity. Therefore, while non-gradient, uniformly needle-punched carbon fiber reinforced composites can achieve excellent ablation protection performance, their weight and mechanical load-bearing capacity are difficult to satisfy simultaneously.

[0021] The laminated and stitched carbon fiber preform is prepared by laying up carbon fiber fabrics using different weaving methods and then stitching the carbon fibers together in the Z-direction. This type of carbon fiber preform has a high carbon fiber content and a longer continuous fiber length compared to needle-punched preforms. Furthermore, due to the tight connection between the carbon fiber fabrics, the internal pores are connected by numerous small throats, making fluid passage relatively difficult. Ceramic-modified composite materials prepared from laminated and stitched carbon fiber preforms exhibit excellent load-bearing capacity due to their high carbon fiber volume content and continuous fiber structure. However, because the matrix carbon fills the small gaps between the carbon fibers during the preform densification process, the carbon inside the ceramic-modified composite material is usually continuously distributed. This continuous carbon is easily lost through continuous oxidation by oxygen in the high-temperature ablation environment. The internal ceramic phase, failing to adequately encapsulate the carbon, cannot perform its ablation protection function, thus limiting the ablation protection performance of such materials and making it difficult to simultaneously meet the three requirements mentioned above.

[0022] Both types of non-gradient composite materials can fulfill some functions under high-temperature environments. For example, needle-punched precast composite materials provide excellent ablation protection, while laminated stitched precast composite materials effectively perform load-bearing functions. However, neither can simultaneously meet the multiple requirements of ablation, load-bearing capacity, and weight reduction.

[0023] The preferred graded-structure needle-stitched carbon fiber preform prepared in this invention integrates two different carbon fiber preforms with needle-punched and stitched structures, creating a carbon fiber preform with multiple graded structures. This allows for multifunctional partitioning and synergy within the same material. The outer layer directly faces the ultra-high temperature environment, requiring control of its porosity and fiber structure to achieve excellent ablation protection after ceramic modification. The inner layer primarily serves for load bearing while simultaneously achieving weight reduction in the composite material. The needle-punched structure, after ceramic modification, yields excellent ablation protection performance; therefore, a needle-punched structure is chosen as the preform for the outer layer. The stitched structure, due to its high carbon fiber content and high continuity, is selected as the inner layer preform to achieve load bearing.

[0024] In a further preferred embodiment, in the laminated and stitched carbon fiber preform, on the side away from the 2.5D needle-punched carbon fiber preform, the carbon fiber woven fabric is selected from satin and / or plain weave fabric, and on the side closer to the 2.5D needle-punched carbon fiber preform, the carbon fiber woven fabric is a spread fabric.

[0025] In a further preferred embodiment, the number of layers of the expanded fabric in the laminated and stitched carbon fiber preform is 1-8 layers, preferably 1-4 layers, and even more preferably 2-3 layers.

[0026] Experiments have shown that using a widened fabric on the side near the 2.5D needle-punched carbon fiber preform can serve as a barrier layer between the 2.5D needle-punched carbon fiber preform and other parts of the laminated carbon fiber preform. This prevents fluid from directly penetrating into the laminated structure through the connecting pores in the middle during the modification of the outer needle-punched preform by the ceramic, thus reducing the mechanical properties of the laminated structure and causing an unnecessary increase in the density of this part of the material.

[0027] Using the complete gradient-structured carbon fiber preform prepared above, non-uniform gradient CVI densification is performed from the lamination-stitched side based on unidirectional CVI technology. This rapidly increases the density of the preform in the lamination-stitched structure to achieve sufficient mechanical load-bearing capacity. Simultaneously, the intermediate barrier layer prevents the permeation of reactive gases into the needled structure side during CVI, maintaining a lower density on the needled structure side to accommodate more ceramic phase during subsequent ceramic phase modification, thus achieving the required ablation protection capability. The gradient-structured carbon fiber preform obtained after unidirectional CVI non-uniform densification is then used to introduce the ceramic phase from the outer surface of the needled structure into the gradient-structured carbon fiber preform using unidirectional RMI, allowing the ceramic phase to fully fill the pores in the needled structure preform. Due to the presence of the barrier layer, there is no large amount or even no ceramic phase infiltration on the lamination-stitched side, ultimately maintaining the characteristics of a low-density but high-strength C / C composite material. Thus, through the synergistic regulation of unidirectional CVI and unidirectional RMI, an outer high-ceramic-content ablation protection zone and an inner low-density pure C / C load-bearing weight-reducing zone were successfully constructed within a gradient structure preform. This fundamentally solves the inherent problem of functional and density mismatch in non-gradient homogeneous structures, achieving the simultaneous fulfillment of all three requirements. This is a goal that is difficult or even impossible to achieve using a single, homogeneous carbon fiber preform.

[0028] The gradient-structure carbon fiber reinforced ceramic-modified composite material prepared based on the above process achieves a perfect match between function, structure, and density. Its surface layer uses a needle-punched structure, and after modification with ultra-high temperature ceramics, it achieves excellent ablation protection. The inner layer uses a laminated stitching structure, and after unidirectional CVI densification, it maintains a low overall density but has sufficient mechanical load-bearing capacity, achieving the goal of low density and high specific strength. This gradient structure achieves the goal of providing ablation protection with a high-density outer ceramic-modified composite material and providing mechanical load-bearing capacity with a low-density inner C / C composite material. This fundamentally solves the problem that non-gradient structure composite materials cannot simultaneously meet multiple requirements and achieve the goal of surface-to-inner layer function and density mismatch. Furthermore, using a gradient-structure carbon fiber preform, combined with subsequent unidirectional CVI densification and unidirectional RMI modification, offers advantages such as a simple preparation process and short preparation cycle, advantages that are difficult to achieve with a single-structure carbon fiber preform.

[0029] In a further preferred embodiment, in S1, the suture density of the Z-direction suture is between 3mm×3mm and 15mm×15mm.

[0030] In a further preferred embodiment, the thickness of the laminated and stitched carbon fiber preform is 3~30mm.

[0031] More preferably, the density of the laminated and stitched carbon fiber preform is 0.7~1 g / cm³. 3In this invention, the laminated and stitched carbon fiber preform has a high density, resulting in a high proportion of carbon fiber content after densification, thereby achieving excellent mechanical properties.

[0032] In a further preferred embodiment, in S2, the needle-punching density of the 2.5D needle-punched carbon fiber preform ranges from 15 to 30 needles / cm along the direction from contact with the laminated and stitched carbon fiber body to the direction away from it. 2 Decrease to 8 or more stitches per cm and less than 15 stitches per cm 2 Preferably, it has 15-25 stitches / cm 2 Decrease to 8-12 stitches / cm 2 .

[0033] This invention further utilizes a gradient change in needled density to effectively form Z-direction fibers and Z-direction interconnecting channels in both needled and laminated stitched structures. Through a unidirectional reactive melting and infiltration method, after modifying the 2.5D needled structure preform with ultra-high temperature ceramics, a portion of the molten metal can infiltrate into the laminated stitched structure through the Z-direction interconnecting channels formed by needled insertion. This portion of the ceramic phase can also generate pinning and mechanical bonding effects, thereby improving the interfacial bonding strength of the composite material with its two different structures: the needled structure and the laminated stitched structure.

[0034] In a further preferred embodiment, in S2, the thickness of the single-layer mesh layer in the 2.5D needle-punched carbon fiber preform increases gradually from 0.2~0.6mm to 0.8~2mm along the direction from contact with the laminated and stitched carbon fiber body to the direction away from it.

[0035] In this invention, the thickness of the mesh layer and the needle-punching density exhibit opposite trends. This synergistic effect results in a greater number of Z-axis fibers within the preform, leading to a relatively higher interlayer bonding strength. After melt infiltration, a thicker mesh layer results in a higher ceramic phase content in the composite material, and vice versa. The ceramic phase content significantly affects ablation protection performance and the coefficient of thermal expansion. This invention uses a thicker mesh layer on the outer layer to accommodate more ceramic phase, achieving superior ablation protection performance, while using a thinner mesh layer on the inner layer to reduce the ceramic phase content. This aims to reduce the coefficient of thermal expansion of this portion of the material, alleviate interfacial shear stress concentration, and improve the interlayer bonding strength of the two composite materials with different structures.

[0036] In a further preferred embodiment, in S2, the density of the 2.5D needle-punched carbon fiber preform ranges from 0.5 to 0.8 g / cm³ along the direction from contact with the laminated and stitched carbon fiber body to its distance from contact. 3 Reduced to 0.3~0.5 g / cm³ 3 .

[0037] In a further preferred embodiment, in S2, the total thickness of the 2.5D needle-punched carbon fiber preform is 3~50mm, preferably 3~30mm.

[0038] In a further preferred embodiment, the layup angle of adjacent non-woven fabrics in the 2.5D needle-punched carbon fiber preform is 0° / 90°.

[0039] More preferably, the Z-direction suture lines in S1 and S2 coincide, or the suture position of S2 is located at the exact center of the suture line of the laminated carbon fiber preform, preferably the Z-direction suture lines in S1 and S2 coincide.

[0040] This invention reduces damage to carbon fibers in the laminated preform by aligning the suture lines, while placing the suture line at the exact center of the laminated carbon fiber preform improves the interlayer bonding strength of the composite material in the laminated structure.

[0041] In a preferred embodiment, the clamping cavity area of ​​the porous graphite plate is provided with a plurality of vent holes, the diameter of which is 5-20mm, and the distance between the central axes of adjacent vent holes is 1-5 times the diameter of the vent holes.

[0042] Experiments have shown that the vents serve the function of venting the gas exchange in the CVI process. Controlling the diameter and spacing of the vents within the above-mentioned range not only results in the highest deposition efficiency but also in the most ideal gradient structure obtained from the final deposition, leading to the best performance of the resulting composite material.

[0043] In a further preferred embodiment, the array structure of the vent holes is rectangular or circular.

[0044] In a further preferred embodiment, when the length of the porous graphite plate is ≥2000mm, the vent hole has two aperture sections along its axial direction. The aperture of the first aperture section that contacts the solid graphite plate is 5-15mm, and the aperture of the first aperture section that is away from the solid graphite plate is 16-20mm. The depth of the first aperture section accounts for 1 / 3-1 / 2 of the thickness of the porous graphite plate.

[0045] Experiments have shown that when the size of the porous graphite plate is large, the gradient holes can shorten the gas exchange distance that the reactant gas has to travel through the small aperture through the large holes, thereby increasing the gas exchange efficiency and thus increasing the CVI efficiency. At the same time, since the depth of the large holes is limited, the thickness of the small holes can still provide a certain rigidity retention capacity, avoiding the deformation problem during the CVI process, which further improves the rigidity retention capacity of the graphite plate.

[0046] In a preferred embodiment, the back of the deposition fixture is provided with reinforcing ribs. By providing reinforcing ribs, it is ensured that the center of the larger graphite fixture still has sufficient rigidity to provide sufficient clamping strength to guarantee the dimensional stability of the C / C preform when in use.

[0047] In a preferred embodiment, when several deposition fixtures containing carbon fiber preforms are placed at intervals in a chemical vapor deposition furnace, the spacing between two adjacent deposition fixtures is kept consistent, and the porous graphite plates in any two deposition fixtures are oriented in the same direction.

[0048] or;

[0049] Several deposition fixtures containing carbon fiber preforms are placed in a chemical vapor deposition furnace in pairs, with one side of a solid graphite plate attached to each other, ensuring that the spacing between any two sets of deposition fixtures is consistent.

[0050] By arranging the above-mentioned tooling and coordinating the flow of the reaction gas only from the area between the porous graphite plates, a stable and consistent flow field of the reaction gas can be ensured.

[0051] In a preferred embodiment, during the chemical vapor deposition process, propylene is used as the carbon source gas, nitrogen is used as the dilution gas, the volumetric flow rate ratio of propylene to nitrogen is 2.5~3.5:1, the temperature is 900~980℃, the pressure is 0.6-1.0kPa, and the deposition time is 20-1000h, preferably 20-200h.

[0052] In a preferred embodiment, the gap between the bottom surface of the graphite crucible and the high-density surface of the carbon-carbon porous body is controlled at 3-30 mm, and the gap between the sidewall of the graphite crucible and the side surface of the carbon-carbon porous body is controlled at 0.2-3 mm. A graphite frame, in close contact with the upper surface of the C / C preform, is placed above the low-density surface of the preform, and a certain pressure is applied to the graphite frame to ensure good contact between the graphite frame and the low-density surface of the preform.

[0053] Experiments revealed that maintaining a limited gap between the graphite crucible and the side of the carbon-carbon porous body effectively prevents the sample from breaking the graphite crucible due to the difference in thermal expansion coefficients between the sample and the graphite crucible during unidirectional RMI. Placing the graphite frame on the low-density surface allows the melt to penetrate unidirectionally into the C / C preform only from the low-density side, preventing it from penetrating into the sample from the side. The gap between the high-density surface of the carbon-carbon porous body and the bottom surface of the graphite crucible ensures that even if some melt penetrates to the bottom of the crucible, it will not seep back into the carbon-carbon porous body from the high-density side. This ensures a unidirectional infiltration path and the formation of a unidirectional distribution gradient of the ceramic phase, while also enhancing the adaptability to unexpected conditions during the preparation process.

[0054] A further preferred embodiment is to provide a graphite gasket between the bottom surface of the graphite crucible and the high-density surface of the carbon-carbon porous body, or to use a graphite crucible with steps at the bottom corners, thereby creating a gap between the bottom surface of the graphite crucible and the high-density surface of the carbon-carbon porous body.

[0055] A further preferred embodiment involves using a graphite crucible whose shape and dimensions match those of the carbon-carbon porous body, and filling the gaps between the sidewalls of the graphite crucible and the sides of the carbon-carbon porous body with graphite paper. This fixes the sample's position within the graphite crucible, ensuring that it does not move during sample and crucible transfer.

[0056] In a preferred embodiment, a bottomless graphite frame is attached and placed above the low-density surface. The planar dimension of the inner cavity of the graphite frame is not greater than the planar dimension of the low-density surface of the carbon porous body, and the horizontal projection of the inner cavity of the graphite frame is controlled to fall completely within the surface contour of the low-density surface of the carbon porous body.

[0057] The size and placement of the graphite frame are designed to ensure its effective barrier against the melt. The external dimensions of the graphite frame can be similar to or different from the internal dimensions of the graphite crucible. If similar, graphite paper can be filled around the outside of the frame and inside the crucible to fix their relative positions. If different, other graphite blocks can be used to fill the gaps, and graphite paper can be used to fill small gaps to secure the crucible. If necessary, a certain pressure needs to be applied to the graphite frame to ensure a tight fit between the frame and the low-density surface. Wedge-shaped graphite blocks can be used to provide pressure while fixing the frame, or a graphite block can be applied above the frame after the infiltration material is filled to ensure a tight fit between the frame and the low-density surface. The infiltration material is placed inside the graphite frame.

[0058] In this invention, the graphite frame can effectively confine the molten material during the melting and infiltration process within the graphite frame, thereby achieving unidirectional melting and infiltration only from top to bottom into the preform within the graphite frame.

[0059] In a further preferred embodiment, the thickness of the graphite frame is 3-10 mm. This ensures that when it is tightly fitted to the upper part of the low-density surface, it can effectively prevent excessive leakage of melt from the junction of the graphite frame and the low-density surface during the reactive infiltration process.

[0060] In a preferred embodiment, the reaction melting is carried out under a protective atmosphere such as argon or a vacuum atmosphere.

[0061] In actual operation, the melting temperature and atmosphere vary depending on the components being melted. When the metal powder contains Si, an inert atmosphere with argon as the main gas is used for melting; when it does not contain Si, vacuum is preferred for melting.

[0062] Compared with the prior art, the method for preparing gradient structure carbon fiber reinforced ceramic modified composite materials provided by the present invention has at least the following significant advantages:

[0063] (1) Precise control of gradient structure: Through the synergistic effect of two key steps, “unidirectional CVI” and “unidirectional RMI”, this invention can precisely control the internal density and gradient distribution of the ceramic phase in the composite material. The unidirectional CVI process, by controlling the flow direction of the reactive gas and the CVI densification temperature, can form a precise density gradient in the densification stage of the C / C composite material; the subsequent unidirectional RMI process utilizes this density gradient to guide the molten metal to penetrate only from the low-density region, ultimately forming a gradient structure in which the ceramic phase gradually decreases from the near end to the far end of the melting penetration. This preparation process has a clear design concept and strong controllability.

[0064] (2) Simple process and low cost: This invention mainly relies on specially made graphite tooling (such as porous graphite plate, solid graphite plate, graphite crucible) and simple packaging materials (such as graphite paper, carbon felt) to achieve unidirectional CVI densification and melting effect. It does not require complex equipment or expensive consumables. The whole process is easy to operate and scale up, which is conducive to industrial production and reduces manufacturing costs.

[0065] (3) Composite materials prepared by one-time molding can have both ablation protection and mechanical load-bearing functions: The composite material prepared by the method of this invention can have a gradient structure that can be customized according to actual application requirements. For example, a carbon fiber preform with a gradient structure, which is integrally formed from a 2.5D needle-punched carbon fiber preform and a laminated and stitched carbon fiber preform, can be densified by CVI, so that the laminated and stitched structure side has a high density while the 2.5D needle-punched carbon fiber preform side has a low density. Then, in the subsequent unidirectional RMI process, a ceramic phase is introduced into the low-density 2.5D needle-punched carbon fiber preform side to make a gradient composite material with a gradient distribution of ceramic phase, carbon fiber structure and pore structure, which takes into account both ablation protection performance and high-temperature mechanical load-bearing performance.

[0066] (4) The method of the present invention is not limited to a specific carbon fiber preform shape or size. It can be applied to preforms of various shapes such as block and plate, and has good compatibility with the composition of metal powder (such as containing Si or not containing Si). It can be achieved by adjusting the melting atmosphere, showing strong versatility. Attached Figure Description

[0067] Figure 1 This is a schematic diagram of the porous graphite tooling used in this invention.

[0068] Figure 2 It is a real-life image showing how graphite paper, carbon felt, and graphite rope are used to seal all sides except the side that needs to be densified to a high density.

[0069] Figure 3 This is a schematic diagram showing the positions of the preform, graphite crucible, graphite frame, and metal powder in a unidirectional melting process of a flat C / C preform.

[0070] Figure 4 This is the cross-sectional morphology of the gradient C / C porous body obtained after the gradient carbon fiber preform in Example 3 undergoes unidirectional CVI.

[0071] Figure 5 This is the cross-sectional morphology of the gradient carbon fiber reinforced ceramic modified composite material after unidirectional RMI in Example 3.

[0072] Figure 6 This is the cross-sectional morphology of the gradient carbon fiber reinforced ceramic modified composite material prepared using unidirectional CVI and unidirectional RMI in Example 5. Detailed Implementation

[0073] The technical solution of the present invention will be clearly and completely described below through specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise stated, the raw materials and reagents used in the following embodiments are commercially available products, or can be prepared by known methods.

[0074] Example 1

[0075] A preform of unidirectional CVI and unidirectional RMI was prepared using a conventional non-gradient 2.5D needle-punched carbon fiber preform as raw material to prepare a graded composite material. The original density of the 2.5D needle-punched carbon fiber preform was 0.5 g / cm³. 3 The blank is 140mm long and wide, and 10mm thick.

[0076] The carbon fiber preform is wrapped with graphite paper along its sides and one end face without any gaps, exposing only the side requiring high density. The wrapped carbon fiber preform is then clamped in a deposition fixture. The deposition fixture consists of two stacked solid graphite plates and a porous graphite plate, with the carbon fiber preform clamped in a cavity formed between the solid and porous graphite plates. During clamping, the exposed top surface requiring high density is positioned on one side of the porous graphite plate. The cavity area of ​​the porous graphite plate has an array of vent holes, each 10 mm in diameter, with the central axis spacing between adjacent vent holes being twice the diameter of the vent hole.

[0077] Subsequently, four deposition fixtures containing carbon fiber preforms were placed at intervals in a chemical vapor deposition furnace, with the spacing between adjacent fixtures controlled at 30 mm, and the porous graphite plates in any two fixtures facing the same direction. Then, using propylene as the carbon source gas and nitrogen as the diluent gas, chemical vapor deposition was used to periodically densify the carbon fiber preforms. The propylene flow rate was 30±5 L / min, the nitrogen flow rate was 10±2 L / min, the deposition temperature was 930℃, the furnace pressure was maintained between 0.6-1.0 kPa, and the deposition time was 100 h per deposition cycle. After each deposition cycle, the furnace temperature was lowered to below 100℃ before removal from the furnace. The fixtures were removed, and the C / C composite material was taken out. Surface removal processing was performed on one side of the porous graphite fixture to open the closed pores. After processing, the fixtures were re-mounted and deposition was performed again with the same parameters. After five deposition cycles totaling 500 hours, an average density of 1.30±0.05 g / cm³ was obtained. 3 The sample is a C / C porous body with a density gradient along its thickness. During multiple processing steps, the high-density surface requires repeated machining. After the final CVI (Continuous Vibration Instrument) is completed, the sample thickness is retained to 5 mm. Drainage density measurements show that the density of the C / C porous body on the side in contact with the porous graphite plate is 1.32 g / cm³. 3 The density of the C / C porous body on the side in contact with the solid graphite plate is 1.27 g / cm³. 3 .

[0078] After CVI densification, small preforms (100mm × 100mm) of the C / C porous body are cut for unidirectional RMI preparation of ceramic-modified composite materials. These preforms are placed in a graphite crucible with the low-density side facing up and the high-density side facing down. Small graphite blocks are used to elevate the bottom of the graphite crucible relative to the high-density side of the C / C porous body, or the crucible is placed with a stepped bottom, creating a 5mm high pore between the high-density side and the bottom of the crucible. Graphite paper is then used to fill the gaps between the sidewalls of the graphite crucible and the sides of the C / C porous body to secure the C / C porous body within the crucible cavity. A bottomless graphite frame with an outer diameter of 100 × 100mm is placed above the low-density side of the C / C porous body. The frame has a thickness of 10mm and a height of 10mm. The gaps in the inner walls of the graphite frame and graphite crucible were filled with graphite paper or a mixture of graphite blocks and graphite paper to fix the graphite frame inside the graphite crucible, maintaining the relative stability of the crucible, C / C porous body, and graphite frame. The graphite paper filling helps mitigate the problem of crucible or graphite frame breakage caused by differences in the coefficients of thermal expansion between different components. Zr-Hf-Ti mixed powder was then placed inside the graphite frame. The thickness of the Zr-Hf-Ti mixed powder was controlled at 8 mm in the experiment. After completion, the graphite crucible was sealed with a matching graphite crucible lid and transferred to a melting furnace. After shutting down the melting furnace, a vacuum was applied and the seal was measured. Once the seal was satisfactory, the temperature was increased to 2000℃ at a rate of 10℃ / min, and then unidirectional reaction melting was performed under vacuum. During the heating process, the temperature was held at 300℃ and 1300℃ for 30 minutes to ensure uniform temperature inside the furnace cavity. After holding at 2000℃ for 20 minutes, heating was stopped and the furnace was allowed to cool naturally. After cooling to below 300°C, argon gas is added into the furnace and the temperature is further reduced to below 100°C before the sample is removed from the furnace.

[0079] After melt infiltration, the density of the gradient carbon fiber reinforced ceramic modified composite material obtained in Example 1 was 3.58 g / cm³. 3 The bending strength is 158.5 MPa. After a 60s ablation test using a plasma ablation device with an output power of 48 kW, the mass ablation rate is 10.75 mg / s, the mass ablation rate is 1.14 μm / s, and the surface response temperature is in the stable stage, above 2500℃.

[0080] Example 2

[0081] A gradient composite material was prepared by using a 2.5D needle-punched carbon fiber preform with a gradient structure as raw material to produce preforms for unidirectional CVI and unidirectional RMI. The preform has planar dimensions of 323 × 323 mm and a thickness of 10 mm. Based on the thickness of the mesh layer, the preform consists of two layers: a lower layer with a thickness of 7 mm and a single-layer mesh layer with a thickness of 0.5 mm. The lower layer has a density of 0.55 g / cm³.3 The upper layer is 3mm thick, and the single-layer mesh reinforcement is 1mm thick with a density of 0.5g / cm³. 3 .

[0082] The carbon fiber preform is then wrapped with graphite paper along its sides and low-density side without any gaps, exposing only the high-density top surface. The wrapped carbon fiber preform is then clamped in a deposition fixture. The deposition fixture consists of two stacked solid graphite plates and a porous graphite plate, with the carbon fiber preform clamped in a cavity formed between the solid and porous graphite plates. During clamping, the high-density top surface is located on one side of the porous graphite plate, where the cavity area of ​​the porous graphite plate is arrayed with vent holes, each 10mm in diameter, and the distance between the central axes of adjacent vent holes is one time the diameter of the vent hole.

[0083] Subsequently, four deposition fixtures containing carbon fiber preforms were placed at intervals in the chemical vapor deposition furnace, with the spacing between adjacent fixtures controlled at 30 mm, and the porous graphite plates in any two fixtures facing the same direction. Then, using propylene as the carbon source gas and nitrogen as the dilution gas, the carbon fiber preforms were periodically densified using chemical vapor deposition. The propylene flow rate was 30±5 L / min, the nitrogen flow rate was 10±2 L / min, the deposition temperature was 930℃, and the pressure inside the deposition furnace was maintained between 0.6-1.0 kPa. Each deposition cycle lasted 100 hours. After each deposition cycle, the furnace temperature was lowered to below 100℃ before removal from the furnace. The fixtures were removed, and the C / C composite material was taken out. Surface removal processing was then performed on one side of the C / C composite material containing the porous graphite preform, as required, to open the closed pores. After surface processing, the fixtures were re-mounted and the furnace was reloaded using the same parameters for CVI (Continuous Vibration Injection). After a total deposition of 500 hours, an average density of 1.31 g / cm³ was obtained. 3 It is a C / C porous body with a density gradient along its thickness. The density of the C / C porous body on the side in contact with the porous graphite plate can reach 1.34 g / cm³. 3 The density of the C / C porous body on the side in contact with the solid graphite plate is 1.27 g / cm³. 3 After CVI is completed, the thickness of the C / C composite material is 5.5 mm, with the upper layer still being 3 mm thick.

[0084] After completing CVI, the aforementioned C / C composite material is processed into a preform with a planar dimension of 100mm × 100mm for subsequent unidirectional RMI. This preform is placed in a graphite crucible with its low-density side facing up and its high-density side facing down, in a graphite crucible of appropriate size. Small graphite blocks are used to elevate the bottom surface of the graphite crucible and the high-density surface of the carbon-carbon porous body, or the crucible is placed in a graphite crucible with a stepped bottom, creating a pore height of 5mm between the high-density surface and the bottom of the graphite crucible. Then, graphite paper is used to fill the gaps between the sidewalls of the graphite crucible and the sides of the carbon-carbon porous body to fix the C / C porous body within the graphite crucible cavity. A bottomless graphite frame is placed above the low-density surface of the carbon-carbon porous body. The outer diameter of this graphite frame is equal to the area of ​​the C / C porous body used for melting and infiltration (length and width are both 100mm). The height of this graphite frame is set to 10mm. The graphite frame and the inner wall of the graphite crucible are filled with graphite paper or graphite blocks and graphite paper to fix the graphite frame in the graphite crucible, maintaining the relative positions of the crucible, C / C porous body, and graphite frame. Then, Zr-Hf-Ti mixed powder is placed inside the graphite frame, with the Zr-Hf-Ti mixed powder layer thickness controlled at 8 mm. After completion, the graphite crucible is sealed and transferred to a melting furnace. After the melting furnace is shut down, it is evacuated and the seal is measured. After the seal is deemed satisfactory, the temperature is increased to 2000℃ at a rate of 10℃ / min for reaction melting. During melting, the temperature is maintained at 300℃ and 1300℃ for 30 minutes to ensure uniform temperature inside the furnace. After holding at 2000℃ for 20 minutes, heating is stopped and the furnace is cooled down. Once the temperature drops below 300℃, argon gas is added to the furnace, and the temperature is further cooled to below 100℃ before the sample is removed from the furnace.

[0085] After melt infiltration, the density of the ceramic-based carbon fiber reinforced composite material obtained in Example 2 was 3.83 g / cm³. 3 Using a plasma ablation device with an output power of 48 kW, a 60-second ablation test was conducted. The mass ablation rate was 8.25 mg / s, the ablation rate at the ablation centerline was -1.37 μm / s, and the ablation temperature was 2500℃.

[0086] Example 3:

[0087] A gradient composite material was prepared using a needle-punched-stitched carbon fiber preform with a gradient structure as the raw material to produce preforms for unidirectional CVI and unidirectional RMI. The needle-punched-stitched carbon fiber preform with this gradient structure has dimensions of 323 × 323 mm, and its preparation process is as follows:

[0088] (1) A layered and stitched carbon fiber preform was prepared by progressively laying down eight-end satin-weave carbon fiber fabric to a thickness of 10 mm, followed by stitching with 1 kJ continuous carbon fiber at a Z-direction spacing of 10 mm × 10 mm. After preparation, the density of the stitched carbon fiber preform was 0.85 g / cm³. 3.

[0089] (2) First, lay a 1mm thick layer of chopped fibers, then lay a 0° non-woven fabric on top of the chopped fibers, and then lay another layer of chopped fibers on top of the non-woven fabric to a thickness of 1mm, followed by needle punching. Then lay a 90° non-woven fabric on top, and then continue laying a layer of chopped fibers to a thickness of 1mm, and then perform needle punching. The needle punching depth is 3mm. Repeat the above process until the thickness of the 2.5D needle-punched carbon fiber preform reaches 10mm.

[0090] (3) The 2.5D needle-punched carbon fiber preform prepared above is stacked on top of the laminated carbon fiber preform and integrally stitched in the Z direction using continuous fibers (polyacrylonitrile (PAN) based carbon fiber, 1K). The mesh layer is attached to the laminated carbon fiber preform on one side. The stitching spacing is 10mm×10mm, and the carbon fiber thread is located at the center of the stitching of the laminated carbon fiber preform.

[0091] The carbon fiber preform and the needle-punched preform are then wrapped with graphite paper without gaps, exposing only the top surface of the laminated and stitched structure. The wrapped carbon fiber preform is then clamped in a deposition fixture. The deposition fixture consists of a solid graphite plate and a porous graphite plate stacked on top of each other, with the carbon fiber preform clamped in a cavity formed between the solid and porous graphite plates. During clamping, one side of the laminated and stitched carbon fiber preform is positioned on the side of the porous graphite plate, where the cavity area of ​​the porous graphite plate is arrayed with vent holes, each 10 mm in diameter, and the distance between the central axes of adjacent vent holes is one time the diameter of the vent hole.

[0092] Subsequently, four deposition fixtures containing carbon fiber preforms were placed at intervals in the chemical vapor deposition furnace, with the spacing between adjacent fixtures controlled at 30 mm, and the porous graphite plates in any two fixtures facing the same direction. Then, using propylene as the carbon source gas and nitrogen as the dilution gas, the carbon fiber preforms were periodically densified using chemical vapor deposition. The propylene flow rate was 30±5 L / min, the nitrogen flow rate was 10±2 L / min, the deposition temperature was 930℃, the furnace pressure was controlled between 0.6-1.0 kPa, and the single deposition time was 100 h. After each deposition, the furnace temperature was lowered to below 100℃ before removal from the furnace. The fixtures were removed, and the C / C composite material was taken out. Surface removal processing was performed on one side of the porous graphite fixture to open the closed pores. Then, the fixture clamping, sample placement, and unidirectional CVI process were repeated according to the above procedure. After a total deposition time of 500 hours, an average density of 1.31 g / cm³ was obtained. 3 It is a C / C porous body with a density gradient along its thickness. The density of the C / C porous body on the side in contact with the porous graphite plate can reach 1.48 g / cm³. 3The C / C porous body density on the side in contact with the solid graphite plate is maintained at 1.24 g / cm³. 3 .

[0093] After completing the unidirectional CVI, the thickness on one side of the laminated stitch structure is maintained at 5.5 mm, and the thickness on the other side of the needle-punched structure is maintained at 3 mm; part of it is cut into preforms with a planar size of 100×130 mm for unidirectional RMI.

[0094] A carbon-carbon porous body is placed in a graphite crucible with the low-density (2.5D) needle-punched C / C porous body facing upwards and the layered stitched C / C porous body facing downwards. Small graphite blocks are used to elevate the bottom of the graphite crucible and the high-density surface of the carbon-carbon porous body, or the body is placed in a graphite crucible with a stepped bottom, creating pores of 5mm in height between the high-density surface and the bottom of the graphite crucible. Graphite paper is then used to fill the gaps between the sidewalls of the graphite crucible and the sides of the carbon-carbon porous body to secure the C / C porous body within the graphite crucible cavity. A bottomless graphite frame is placed above the low-density surface of the carbon-carbon porous body. The outer diameter of this graphite frame is equal to the area of ​​the C / C porous body used for melting and infiltration, and is 100 × 130 mm. The thickness of this graphite frame is set to 10 mm. The graphite frame and the inner wall of the graphite crucible are filled with graphite paper or graphite blocks and graphite paper to fix the graphite frame in the graphite crucible, maintaining the relative position of the crucible, C / C porous body, and graphite frame. Then, Zr-Hf-Ti mixed powder is placed inside the graphite frame, with the Zr-Hf-Ti mixed powder layer thickness controlled at 9 mm. After completion, the graphite crucible is sealed and transferred to a melting furnace. After the melting furnace is closed, it is evacuated and the seal is measured. Once the seal is satisfactory, the temperature is increased to 2000℃ at a rate of 10℃ / min for reaction melting. During melting, the temperature is maintained at 300℃ and 1300℃ for 30 minutes to ensure uniform temperature inside the furnace. Finally, heating is stopped after holding at 2000℃ for 20 minutes, and the furnace is cooled down. After cooling to below 300℃, argon gas is added to the furnace, and the temperature is further reduced to below 100℃.

[0095] After melt infiltration, the density of the gradient carbon fiber reinforced ceramic modified composite material obtained in Example 3 was 3.09 g / cm³. 3 The density reduction is more than 15% compared to Example 2.

[0096] Using a plasma ablation device with an output power of 48 kW, a 60-second ablation test was conducted. The linear ablation rate was 5.72 μm / s, the mass ablation rate was 7.92 mg / s, and the surface response temperature during stable ablation was above 2600℃.

[0097] The gradient carbon fiber reinforced ceramic modified composite material has a flexural strength of 260.6 MPa and a flexural modulus of 22528.08 MPa at 2000℃.

[0098] Example 4:

[0099] Gradient composite materials were prepared using unidirectional CVI and unidirectional RMI preforms made from a gradient-structured needle-punched-laminated carbon fiber preform. The dimensions of this gradient-structured needle-punched-laminated carbon fiber preform were 323 × 323 mm, and its preparation process is as follows:

[0100] (1) A layered and stitched carbon fiber preform was prepared by progressively laying down eight-end satin-weave carbon fiber fabric to a thickness of 10 mm, followed by stitching with 1 kJ continuous carbon fiber at a Z-direction spacing of 10 mm × 10 mm. After preparation, the density of the stitched carbon fiber preform was 0.85 g / cm³. 3 .

[0101] (2) First, lay a 0° non-woven fabric, then lay a layer of chopped fibers on the non-woven fabric to a thickness of 0.3 mm. Next, lay a 90° non-woven fabric on top of the chopped fiber mesh layer, and then continue laying chopped fibers to a thickness of 0.3 mm. Then, perform needle punching with a needle to a depth of 3 mm. Repeat the above process until the thickness of the 2.5D needle-punched carbon fiber preform reaches 3 mm. Then, increase the thickness of the chopped fiber layer to 1 mm, performing needle punching after each layer of chopped fibers, until the total thickness of the 2.5D needle-punched carbon fiber preform is 10 mm. The density per unit thickness of the preform increases from 0.6 g / cm³ from bottom to top. 3 Reduced to 0.4 g / cm³ 3 The needle-punching density increases from 15 needles / cm along the direction from where it meets the laminated and stitched carbon fiber preform to the direction away from it. 2 2 needles / cm 2 Decrease to 9 stitches / cm 2 .

[0102] (3) The 2.5D needle-punched carbon fiber preform prepared above is stacked on top of the laminated carbon fiber preform and integrally stitched in the Z direction using continuous fibers (polyacrylonitrile (PAN) based carbon fiber, 1K). The side with a mesh layer thickness of 0.3 mm is attached to the laminated carbon fiber preform. The stitching spacing is 10 mm × 10 mm, and the carbon fiber thread is located at the center of the stitching of the laminated carbon fiber preform.

[0103] The carbon fiber preform and the needle-punched preform are then wrapped with graphite paper without gaps, exposing only the top surface of the laminated and stitched structure. The wrapped carbon fiber preform is then clamped in a deposition fixture. The deposition fixture consists of a solid graphite plate and a porous graphite plate stacked on top of each other, with the carbon fiber preform clamped in a cavity formed between the solid and porous graphite plates. During clamping, one side of the laminated and stitched carbon fiber preform is positioned on the side of the porous graphite plate, where the cavity area of ​​the porous graphite plate is arrayed with vent holes, each 10 mm in diameter, and the distance between the central axes of adjacent vent holes is one time the diameter of the vent hole.

[0104] Subsequently, four deposition fixtures containing carbon fiber preforms were placed at intervals in the chemical vapor deposition furnace, with the spacing between adjacent fixtures controlled at 30 mm, and the porous graphite plates in any two fixtures facing the same direction. Then, using propylene as the carbon source gas and nitrogen as the dilution gas, the carbon fiber preforms were periodically densified using chemical vapor deposition. The propylene flow rate was 30±5 L / min, the nitrogen flow rate was 10±2 L / min, the deposition temperature was 930℃, the furnace pressure was controlled between 0.6-1.0 kPa, and the single deposition time was 100 h. After each deposition, the furnace temperature was lowered to below 100℃ before removal from the furnace. The fixtures were removed, and the C / C composite material was taken out. Surface removal processing was performed on one side of the porous graphite fixture to open the closed pores. Then, the fixture clamping, sample placement, and unidirectional CVI process were repeated according to the above procedure. After a total deposition time of 500 hours, an average density of 1.31 g / cm³ was obtained. 3 It is a C / C porous body with a density gradient along its thickness. The density of the C / C porous body on the side in contact with the porous graphite plate can reach 1.48 g / cm³. 3 The C / C porous body density on the side in contact with the solid graphite plate is maintained at 1.24 g / cm³. 3 .

[0105] After completing the unidirectional CVI, the thickness on one side of the laminated stitch structure is maintained at 5.5 mm, and the thickness on the other side of the needle-punched structure is maintained at 3 mm. Then, part of it is cut into carbon porous bodies with a planar size of 100×130 mm, which are used as preforms for unidirectional RMI.

[0106] A carbon-carbon porous body is placed in a graphite crucible with the lower 2.5D needle-punched C / C porous body facing upwards and the layered stitched C / C porous body facing downwards. Small graphite blocks are used to elevate the bottom surface of the graphite crucible and the high-density surface of the carbon-carbon porous body, or the body is placed in a graphite crucible with a stepped bottom, creating pores of 5 mm in height between the high-density surface and the bottom of the graphite crucible. Then, graphite paper is used to fill the gaps between the sidewalls of the graphite crucible and the sides of the carbon-carbon porous body to fix the C / C porous body within the inner cavity of the graphite crucible. A bottomless graphite frame is placed above the low-density surface of the carbon-carbon porous body. The outer diameter of the graphite frame is equal to the area of ​​the C / C porous body used for melting and infiltration, which is 100 × 130 mm. The thickness of the graphite frame is set to 10 mm, and the height is set according to the height of the melting and infiltration material to be filled. The graphite frame and the inner wall of the graphite crucible are filled with graphite paper or graphite blocks and graphite paper to fix the graphite frame in the graphite crucible, maintaining the relative fixed positions of the crucible, C / C porous body, and graphite frame. Then, Zr-Hf-Ti mixed powder is placed inside the graphite frame, and the thickness of the Zr-Hf-Ti mixed powder is controlled to be 9 mm. After completion, the graphite crucible is sealed and transferred to the melting and infiltration furnace. After the melting and infiltration furnace is closed, the furnace is evacuated and the sealing performance is measured. After the sealing performance meets the standard, the temperature is increased to 2000℃ at a rate of 10℃ / min, and the reaction melting and infiltration is carried out. During the melting and infiltration process, the temperature is kept constant at 300℃ and 1300℃ for 30 min to ensure the temperature uniformity inside the furnace cavity. After holding at 2000℃ for 20 minutes, heating was stopped and the furnace was cooled down. After the temperature dropped to below 300℃, argon gas was added into the furnace and the temperature was further cooled to below 100℃ before the sample was removed from the furnace.

[0107] After melt infiltration, the density of the gradient carbon fiber reinforced ceramic modified composite material in Example 4 was 2.96 g / cm³. 3 Using a plasma ablation device with an output power of 48 kW for 60 seconds, the linear ablation rate was -3.85 μm / s, and the mass ablation rate was 3.15 mg / s. The flexural strength of the laminated and stitched carbon fiber reinforced composite material at 2000℃ was 271 MPa.

[0108] Example 5

[0109] The other conditions are the same as in Example 4, except that the two layers of satin fabric connecting the laminated and sewn carbon fiber preform to the 2.5D needle-punched preform are replaced with spread fabric. Figure 6 The figure shows the cross-sectional morphology of the gradient carbon fiber reinforced ceramic modified composite material prepared by unidirectional CVI and unidirectional RMI in Example 5. As can be seen from the figure, the ceramic phase failed to penetrate into the carbon fiber reinforced composite material with the laminated stitch structure. This indicates that after replacing the two layers of satin fabric with the spread fabric, the molten metal basically does not penetrate into the lower layer of the carbon fiber reinforced composite material with the laminated stitch structure during the unidirectional RMI process.

[0110] The density of the gradient carbon fiber reinforced ceramic modified composite material in Example 5 was measured to be 2.09 g / cm³. 3 Compared to Examples 1 and 2, the reduction was more than 40% each.

[0111] Using a plasma ablation device with an output power of 48 kW, a 60-second ablation test was conducted. The linear ablation rate was -1.37 μm / s, the mass ablation rate was 8.25 mg / s, and the surface response temperature during stable ablation was above 2600℃.

[0112] In addition, the gradient carbon fiber reinforced ceramic modified composite material has a flexural strength of 284.30 MPa and a flexural modulus of 26049 MPa at 2000℃.

[0113] Comparative Example 1

[0114] Other conditions were the same as in Example 1, except that the carbon fiber preform was not wrapped with graphite paper. After unidirectional CVI was completed, no significant density gradient distribution was observed inside the C / C porous body.

[0115] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material, characterized in that: The carbon fiber preform is seamlessly wrapped on all five sides, leaving only one side uncovered to form an exposed surface. It is then clamped in the clamping cavity of the deposition fixture and placed in a chemical vapor deposition furnace for unidirectional chemical vapor deposition to obtain a carbon-carbon porous body with a density gradient decreasing from the exposed surface to the exposed surface. The gradient structure carbon-carbon porous body is then placed in a graphite crucible with the low density surface facing up and the high density surface facing down. A graphite frame is then placed above the low density surface and melt infiltration material is laid inside the frame for unidirectional reactive melt infiltration, thus obtaining a gradient structure ceramic modified carbon fiber reinforced composite material. The deposition fixture includes a solid graphite plate and a porous graphite plate stacked on top of each other, with a clamping cavity formed between the solid graphite plate and the porous graphite plate for clamping the carbon fiber preform; during clamping, the exposed surface of the carbon fiber preform is controlled to be located on one side of the porous graphite plate.

2. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 1, characterized in that: The carbon fiber preform is selected from one of the following: a non-gradient carbon fiber preform, a gradient-structured 2.5 needle-punched carbon fiber preform, and a gradient-structured needle-punched-stitched carbon fiber preform.

3. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 1 or 2, characterized in that: The carbon fiber preform is selected from a gradient structure needle-punched-stitched carbon fiber preform; the needle-punched-stitched carbon fiber preform is a composite of a stitched carbon fiber preform and a 2.5D needle-punched carbon fiber preform; the exposed surface is the end face of the stitched carbon fiber preform.

4. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 3, characterized in that: The method for preparing the gradient-structured needle-stitched carbon fiber preform includes the following steps: S1. Several carbon fiber woven fabrics are stacked and then stitched in the Z direction using continuous fibers to obtain a stacked and stitched carbon fiber preform. S2. The laminated and stitched carbon fiber preform is combined with the 2.5D needle-punched carbon fiber preform. The combination method is as follows: first, a 2.5D needle-punched carbon fiber preform is prepared, then the 2.5D needle-punched carbon fiber preform is laminated with the laminated and stitched carbon fiber preform, and then continuous fibers are used for Z-direction stitching. Alternatively, on one side of the laminated carbon fiber preform, layers of non-woven fabric and mesh are alternately laid and needle-punched together; then continuous carbon fiber is used for Z-direction stitching.

5. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 4, characterized in that: In the laminated and stitched carbon fiber preform, on the side away from the 2.5D needle-punched carbon fiber preform, the carbon fiber woven fabric is selected from satin fabric and / or plain weave fabric, and on the side closer to the 2.5D needle-punched carbon fiber preform, the carbon fiber woven fabric is a spread fabric. In the laminated and stitched carbon fiber preform, the number of layers of the spread fabric is 1-8.

6. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 4, characterized in that: In S1, the suture density of the Z-direction suture is 3mm×3mm-15mm×15mm; The thickness of the laminated and stitched carbon fiber preform is 3~30mm; The density of the laminated and stitched carbon fiber preform is 0.7~1 g / cm³. 3 ; In S2, the needle-punching density of the 2.5D needle-punched carbon fiber preform ranges from 15 to 30 needles / cm along the direction from contact with the laminated and stitched carbon fiber body to the direction away from it. 2 Decrease to 8 or more stitches per cm and less than 15 stitches per cm 2 ; In S2, the thickness of the single-layer mesh layer in the 2.5D needle-punched carbon fiber preform increases from 0.2~0.6mm to 0.8~2mm along the direction from contact with the laminated and stitched carbon fiber body to the direction away from it. In S2, the density of the 2.5D needle-punched carbon fiber preform ranges from 0.5 to 0.8 g / cm³ along the direction from contact with the laminated and stitched carbon fiber body to its distance from contact with it. 3 Reduced to 0.3~0.5 g / cm³ 3 ; In S2, the total thickness of the 2.5D needle-punched carbon fiber preform is 3~50mm; The layup angle of adjacent non-woven fabrics in the 2.5D needle-punched carbon fiber preform is 0° / 90°. The Z-direction sutures in S1 and S2 coincide, or the suture position of S2 is located at the exact center of the suture line of the laminated carbon fiber preform.

7. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 1, characterized in that: The clamping cavity area of ​​the porous graphite plate is provided with several ventilation holes, the diameter of which is 5-20mm, and the distance between the central axes of adjacent ventilation holes is 1-5 times the diameter of the ventilation hole. When the length of the porous graphite plate is ≥2000mm, the vent has two aperture sections along its axial direction. The aperture of the first aperture section that is in contact with the solid graphite plate is 5-15mm, and the aperture of the first aperture section that is away from the solid graphite plate is 16-20mm. The depth of the first aperture section accounts for 1 / 3-1 / 2 of the thickness of the porous graphite plate. The back of the deposition fixture is equipped with reinforcing ribs.

8. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 1, characterized in that: When several deposition fixtures containing carbon fiber preforms are placed at intervals in a chemical vapor deposition furnace, the spacing between two adjacent deposition fixtures is kept consistent, and the porous graphite plates in any two deposition fixtures are oriented in the same direction. or, Several deposition fixtures containing carbon fiber preforms are placed in a chemical vapor deposition furnace in pairs, with one side of a solid graphite plate attached to each other, ensuring that the spacing between any two sets of deposition fixtures is consistent.

9. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 1, characterized in that: In the chemical vapor deposition process, propylene is used as the carbon source gas and nitrogen is used as the dilution gas. The volumetric flow rate ratio of propylene to nitrogen is 2.5~3.5:1; the temperature is 900~980℃; the pressure is 0.6-1.0kPa; and the deposition time is 20-1000h.

10. The method for preparing a gradient-structure carbon fiber reinforced ceramic modified composite material according to claim 1, characterized in that: The gap between the bottom surface of the graphite crucible and the high-density surface of the carbon porous body is controlled at 3-30 mm, and the gap between the side wall of the graphite crucible and the side surface of the carbon porous body is controlled at 0.2-3 mm. A bottomless graphite frame is attached to the top of the low-density surface. The planar dimension of the inner cavity of the graphite frame is not greater than the planar dimension of the low-density surface of the carbon porous body, and the horizontal projection of the inner cavity of the graphite frame is controlled to fall completely within the surface contour of the low-density surface of the carbon porous body. The thickness of the graphite frame is 3-10mm.